ANALISIS KESALAHAN DALAM MENYELESAIAN SOAL BARISAN DAN DERET ARITMATIKA SISWA KELAS XI IPA 7 SMA NEGERI 3 PALU: Analysis Of Errors in Solving Arithmetic Sequences And Series Problems in Class XI IPA 7 Students At SMA Negeri 3 Palu - Ardiansyah, Randy; Hasbi, Muh.; Paloloang, Baharuddin; Pathuddin, Pathuddin (Universitas Tadulako, 2024)
This study aims to obtain a description of student errors in solving arithmetic sequences and series in class XI IPA 7 of SMA Negeri 3 Palu. This type of research is descriptive research. The subjects of this study were 2 students with the most errors taken from 31 students of class XI IPA 7. The errors in this study were divided into three according to the error analysis according to Najiyah, namely conceptual errors, principle errors and operational errors. The data in this study were collected by means of tests and interviews. The data analysis techniques in this study were data condensation, data presentation, and drawing conclusions. The results of the study showed several errors experienced by students in solving arithmetic sequence and series problems, namely: (1) Conceptual errors, namely students did not replace Un with U5, (2) Principle errors, namely students made mistakes in determining the formula and did not know the formula to be used in solving the problem and did not know and did not write the final conclusion, (3) Operational errors, namely students made mistakes in calculating